Training for Improving English Literacy Skills: A Contextual Approach and Competency-Based Curriculum - Lasaiba, Djamila; Lasaiba, Irvan; Partini, Dwi (Jurnal Pengabdian Arumbai, 2024)
Training for community service explores the Enhancement of English Literacy Skills with a Contextual Approach and Competency-Based Curriculum as the foundation for a community service program. Survey and interview methods assess the community's reading, writing, listening, and speaking abilities. The results guide the design of a focused literacy program, including English language skills training and relevant learning resources. Literature reviews emphasize the importance of English literacy in facing global challenges, opening access to knowledge and global educational opportunities and supporting economic and social community growth. The interconnectedness of English literacy with economic, social, cultural, and diplomatic aspects becomes increasingly evident in the era of globalization. Implementing the Contextual Approach and Competency-Based Curriculum has proven effective in enhancing students' motivation and understanding of English. The community service program will leverage these findings by aligning training materials with the students' everyday contexts, integrating competency-based curricula, and utilizing digital technology for digital literacy. This practical approach aims to directly impact participants' English literacy skills, helping them adapt, innovate, and contribute to solutions to global challenges. This program is not just the implementation of research findings but a strategic step towards building a more competent English-speaking community, supporting personal and economic growth in the modern era.